Exploring the genetic of three Hairless Pig breed populations in Mexico - Lemus, Gilberto; Rodríguez, Javier; Burgos, William; Lemus, Clemente; Carmona, Carlos (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2024)
The objective of this research was to carry out a molecular genetic characterization of three Hairless Pig (HP) breed populations located in México in the states of Nayarit, Oaxaca and Yucatán to identify variations, selection effects and population genetic relationships. From blood samples, a total of 163 animals from three populations of HP were successfully genotyped. Genotyped SNP data was employed to compute genetic diversity, population structure and landscape genetic analysis. The parameters of minor allele frequency (MAF), observed heterozygosity (Ho) and Wright’s fixation index (FIS) pointed out that the population of Nayarit is the one with the greatest genetic diversity (MAF: 0.362, Ho: 0.336, FIS: 0.061). Principal Component Analysis (PCA) and a Neighbor-joining phylogenetic tree analysis showed diversification among the three HP populations and pointed out a closer genetic relationship between the HP populations and the Iberian pig breed. The Admixture analysis showed as well common ancestry shared from commercial and Iberian breeds in the HP populations in different gradients. For the analysis of the relationships between geographic and genetic distances, Mantel test was computed and the results described a distribution pattern of the geographical locations along the genetic distances similar to the clustering pattern of the PCA and Neighbor-joining phylogenetic tree analysis. The results obtained manage to present the HP poor conservation state and the need to stablish a genetic conservation program meaning an effort to prevent the loss of a significant cultural, natural and genetic resource.